Professional perspectives on applying the NICE and British Psychological Society Guidelines for the management of Behaviours that Challenge in dementia care: an e‐survey. (22nd June 2021) - Gray, Kristina Lily; Moniz‐Cook, Esme; Reichelt, Katharina; Duffy, Frances; James, Ian Andrew
Abstract : Objectives: Behaviours that challenge (BtC) reflect the most costly and burdensome aspects of dementia where non‐pharmacological interventions rather than antipsychotic medication have been recommended as first‐line approaches for over a decade (NICE 2006). This paper outlines professionals' views about their application of the Dementia NICE Guideline 97 (2018) and a British Psychological Society, Division of Clinical Psychology (BPS‐DCP) Briefing paper (2013) on alternatives to antipsychotics. Methods: A mixed‐methods 34‐item e‐survey, with five items about the use of the NICE Guideline 97 (2018) and the BPS‐DCP Briefing paper (2013) for the management of BtC, was conducted. Participants were recruited through multidisciplinary professional dementia networks across the United Kingdom. Quantitative data were descriptively summarized and thematic analysis of open‐ended questions undertaken. Results: Two hundred and forty‐seven participants completed the questions relating to guidelines. Mean ratings of 'moderately useful' for both the NICE and BPS‐DCP guidance were obtained across professions and geographical locations, with the exception of psychiatrists who rated the NICE guidance as 'slightly useful'. The qualitative themes identified were a mix of positive and cautionary perspectives, relating to 'evidence base', the 'accessibility of the guides', 'problems with implementation', and 'lack of detail and clarity'. Conclusion: Professionals were cautiously positive regarding the guidance for BtC management, but highlighted a need for improved clarity about the use of non‐pharmacological approaches, and more specificity about how these can be implemented in clinical settings. Tailored 'setting‐specific' toolkits are required to update and refine the BPS‐DCP (2013) if the aspirations of the NICE Dementia Guideline 97 (2018) are to inform professional practice. Practitioner Points: Owing to major concerns about the problematic side effects of using psychotropics in the treatment of behaviours that challenge (BtC), there is a need for national guidance on the use on non‐drug alternatives. The NICE (2018) guidance was seen by participants as accessible and clear but lacking in detail in the use of non‐pharmacological interventions, which are the first‐line treatments for BtC. The BPS Guidelines on 'Alternatives to antipsychotics' (2013) were seen as having good structured advice for allocating non‐pharmacological resources but were lacking in flexibility for meeting individual needs or what might be an acceptable fit for clinical services. The findings suggest that we need to develop UK‐wide bespoke specific advice for practitioners and services for both the use and the delivery of non‐pharmacological evidence‐based interventions for BtC.